2022
DOI: 10.3390/cancers14225511
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Profiles for Elucidating Cisplatin Resistance in Head-and-Neck Squamous Cell Carcinoma

Abstract: To identify the novel genes involved in chemoresistance in head and neck squamous cell carcinoma (HNSCC), we explored the expression profiles of the following cisplatin (CDDP) resistant (R) versus parental (sensitive) cell lines by RNA-sequencing (RNA-seq): JHU029, HTB-43 and CCL-138. Using the parental condition as a control, 30 upregulated and 85 downregulated genes were identified for JHU029-R cells; 263 upregulated and 392 downregulated genes for HTB-43-R cells, and 154 upregulated and 68 downregulated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…During clinical treatment, it remains important to consider the impact of CD24 on drug resistance. Several studies have shown that CD24 expression appears to be positively correlated with chemoresistance [84]. RNA sequencing and proteomic analysis of cisplatin-resistant and cisplatin-sensitive head and neck squamous cell carcinoma (HNSCC) identified CD24 as one of the potential genes associated with drug resistance in HNSCC.…”
Section: Clinical Researchmentioning
confidence: 99%
“…During clinical treatment, it remains important to consider the impact of CD24 on drug resistance. Several studies have shown that CD24 expression appears to be positively correlated with chemoresistance [84]. RNA sequencing and proteomic analysis of cisplatin-resistant and cisplatin-sensitive head and neck squamous cell carcinoma (HNSCC) identified CD24 as one of the potential genes associated with drug resistance in HNSCC.…”
Section: Clinical Researchmentioning
confidence: 99%